Early pregnancy exposure to metal mixture and birth outcomes – A prospective study in Project Viva. (November 2021) - Rahman, Mohammad L.; Oken, Emily; Hivert, Marie-France; Rifas-Shiman, Sheryl; Lin, Pi-I D.; Colicino, Elena; Wright, Robert O.; Amarasiriwardena, Chitra; Claus Henn, Birgit G.; Gold, Diane R.; Coull, Brent A.; Cardenas, Andres
Highlights: As, Mn, Pb and Zn in maternal RBC were associated with birth outcomes. Associations varied by infant sex and exposure level of other mixture components. Birth weight lowering effect of As was stronger at higher levels of Mn in males. Head circumference lowering effect of Pb was attenuated at higher levels of Zn. As was associated with lower gestational age at higher levels of Mn and Pb in males. Abstract: Background: Prenatal exposure to metals has been individually associated with birth outcomes. However, little is known about the effect of metal mixture, particularly at low exposure levels. Objectives: To estimate individual and joint effects of metal mixture components on birth outcomes. Methods: We used data from 1, 391 mother-infant pairs in Project Viva (1999–2002). We measured 11 metals in maternal 1st trimester erythrocyte; abstracted birth weight from medical records; calculated gestational age from last menstrual period or ultrasound; and obtained birth length (n = 729) and head circumference (n = 791) from research measurements. We estimated individual and joint effects of metals using multivariable linear and Bayesian kernel machine regressions. Results: In both single metal and metal mixture analyses, exposure to higher concentrations of arsenic was associated with lower birth weight in males, zinc with higher head circumference in females, and manganese with higher birth length in sex-combined analysis. We also observed sex-specific metal interactions with birth outcomes. Arsenic and manganese showed a synergistic association with birth weight in males, in whom an interquartile range (IQR) increase in arsenic was associated with 25.3 g (95% CI: −79.9, 29.3), 47.9 g (95% CI: −98.0, 2.1), and 72.2 g (95% CI: −129.8, −14.7) lower birth weight when manganese concentrations were at 25th, 50th, and 75th percentiles, respectively. Lead and zinc showed an antagonistic association with head circumference in males, where an IQR increase in lead was associated with 0.18 cm (95% CI: −0.35, −0.02), 0.10 cm (95% CI: −0.25, 0.04), 0.03 cm (95% CI: −0.2, 0.14) smaller head circumference when zinc concentrations were at 25th, 50th, and 75th percentiles, respectively. Exposure to higher concentrations of arsenic was also associated with lower gestational age in males when concentrations of manganese and lead were higher. Discussion: Maternal erythrocyte concentrations of arsenic, manganese, lead, and zinc were individually and interactively associated with birth outcomes. The associations varied by infant sex and exposure level of other mixture components.